A DESCRIPTIVE STUDY ON TEACHING VOCABULARY BY USING OUTDOOR ACTIVITIES TO YOUNG LEARNERS AT THE THIRD YEAR IN SD NEGERI 01 GEMPOL KLATEN IN 2006 / 2007 ACADEMIC YEAR - IKASARI , NURHAYATI (2007)
This study aims at describing the process of teaching vocabulary by using outdoor activities at the third year in SD Negeri 01 Gempol. In collecting the data, the writer uses observation and document. Observation is an activity in a certain situation to get the data about the process of teaching vocabulary by using outdoor activities. Document is instrument to collect the data lesson plan. The process about of teaching vocabulary by using outdoor activities is: (1) Before the teacher introduces the new English vocabulary, the students are in the class with the teacher, and then the teacher informs the new English vocabulary that are suitable with the topic in English and the students listen it. (2) Together with the teacher, they go to the location to school's yard. (3) in that location, the teacher will say the things that are suitable with the topic (tree, flower, leaf, grass) (4) The students will also pronounce the word then try to memorize it. (5) After the students know word and know how to pronounce the word. (6) When the lesson is over, the students go back to the class together with the teacher. After collecting data and analyzing them, the writer presented the result of the research. The strength of this method is the students can easily increase their vocabulary and loose their boredom in studying English. The weakness of the method is the student feel tired, because the activities in outdoor are more than one activity. The result of learning vocabulary in outdoor is the student is more creative, their knowledge and motivation can increase. Besides the student can easily increase their vocabulary and lose their boredom in studying English.